Edible Flowers As A Garnish In Food Serving: Knowledge and Cognition of Students of STP AMPTA Yogyakarta Hotel Management Study Program as Research Approach - Nugroho, Setyo Prasiyono; Hermawan Prasetyanto,; Santosa, Vernaldi Agriansyah DS (Technium Social Sciences Journal, 2024)
The objectives of this study are: first, to identify the types of edible flowers which can be used in plating; second, to recognize the knowledge and cognition of the Hotel Management students at STP AMPTA Yogyakarta on the usage of edible plant garnishes for plating. This research is conducted in a qualitative descriptive statistical method. The population and the sample of this research are 30 students of STP AMPTA Yogyakarta majoring in Hotel Management. The sample was collected using a purposive sampling method with the criteria of STP AMPTA students in Hotel Management study program who were taking food processing practice 2 course or students who were in 3rd semester in 2022/2023 academic year, with the total of the respondent of 30 students. The methods of data collecting included in-depth interview, observation, documentation, and literature review. The in-depth interview was conducted with the lecturers (chef) in food processing practice class at STP AMPTA in regard to the types of edible flower used for garnishes. The method used in analysing the data is by describing or presenting the data that had been collected without intending to draw a conclusion that is generally applicable. The data collected is the students’ knowledge and cognition of edible flowers. The result of the study found that the types of edible plant garnishes used in STP AMPTA Yogyakarta are edible leaf (red sorel, nasturtium, pea tendril) and edible flower (viola and pansy). Besides that, the knowledge and cognition indicator revealed the average of variative responses from positive to negative. The average positive responses indicated that they acknowledge the types of edible garnish plants and are confident in putting edible plant garnishes in their plating. Meanwhile, the average of negative responses implicated the students’ lack of information and understanding of flavor and texture of edible plant garnishes they used.